Unveiling Mental Health Perspectives: Nursing Students' Attitudes Towards Spirituality - Sharma, Jigyasha; Rai, Kanika (National Journal of Community Medicine, 2024)
Background: The correlation between spirituality and mental health has transmute a subject of growing significance and importance, particularly within the realms of educational institutions and healthcare facilities. Student nurses encounter difficulties in providing spiritual care to patients and consider it beyond their area of expertise on account of inadequate nursing education and training. The primary objective of this quantitative survey was to ascertain the perceptions and attitudes of nursing students towards spirituality, as well as their perspectives on its integration within their professional practice. Methodology: Eighty subjects were randomly included in the study. The subjects were between 17 to 24 years and belonged to all the four religions. They filled the Likert scale having items pertaining to their attitude towards spirituality. The data analysis was conducted using IBM SPSS version 20. Result: The mean attitude score was 3.71 ± 0.45. Most (69.3%) of the students responded “agree and strongly agree” to the items in the scale reflecting their favorable attitude towards spirituality. The religion significantly affected their attitude (p<0.05). A correlation was also observed between students' religious beliefs and their spiritual orientation. Conclusion: The present study conclude that the students possess a favorable attitude towards spirituality.